Thrombin-Induced Force Development in Vascular Endothelial Cells: Contribution to Alteration of Permeability Mediated by Calcium-Dependent and -Independent Pathways - Koji Nobe; Tomoko Sone; Richard J. Paul; Kazuo Honda (Elsevier, 2005)
Endothelial cell (EC) barrier dysfunction is associated with many types of vascular diseases. Investigators have hypothesized that altered EC contraction in conjunction with morphological changes may lead to EC dysfunction. However, the nature of EC contraction and its regulatory mechanisms are not fully understood. In this study we measured thrombin-induced force in bovine arterial EC force using EC fibers that were grown in a collagen matrix. Contraction, which occurred in time- and dose-dependent fashion, was elicited by thrombin. The thrombin-enhanced EC layer permeability was correlated with EC fiber contraction. These results suggest that EC contractile response is involved in alteration of EC barrier function. During the initial period of thrombin stimulation, cadherin complexes were disrupted and cell-to-cell connections were reduced. This was dependent on the transient increase in intracellular calcium concentration and myosin phosphorylation. Rho kinase activation led to rearrangement of actin stress fibers (ASF). Paracellular holes were created in the EC layer in parallel to EC morphological change. Our findings suggest that EC layer permeability is regulated by two distinguishable steps. In the initial period, the cell-to-cell connection was reduced in a calcium-dependent fashion. Subsequently, Rho kinase and ASF-mediated force development increased EC layer permeability via morphological change of EC. Keywords:: endothelial cell, non-muscle contraction, thrombin, permeability, actin stress fiber